A comparison of pulmonary oxygen uptake kinetics in middle- and long-distance runners - Kilding, A. E.; Winter, E. M.; Fysh, M. (International Journal of Sports Medicine, 2006)
The purpose of this study was two-fold: 1) to compare the on- and off-transient pulmonary oxygen uptake (V·O2) kinetics, in the moderate-intensity domain, of middle-distance (MD) and long-distance (LD) runners and 2) to determine the relationship between the volume of training and V·O2 kinetics. With institutional ethics approval, 16 competitive male MD (800/1500 m) and 16 competitive male LD runners (5000/10 000 m) participated in the study. Each runner completed a series of tests to assess maximal V·O2 (V·O2max), ventilatory threshold (VT), and both the on- and off-transient primary time constants (ton and toff, respectively) in response to moderate-intensity treadmill exercise. The results showed that ton was significantly shorter in LD (12.3 ± 0.5 s) than MD runners (16.4 ± 1.0 s, p = 0.002). During recovery from exercise, toff was shorter in LD than MD runners (toff, 24.3 ± 0.6 s vs. 26.9 ± 0.8 s, p = 0.017). The volume of training was greater in LD (66.6 ± 3.5 km · wk-1) than MD runners (43.5 ± 3.9 km · wk-1, p < 0.001) and was related to ton in both groups of runner (MD: r = - 0.63, p = 0.009; LD: r = - 0.68, p = 0.004). Collectively, the results show that MD and LD runners can be differentiated on the basis of their on- and off-transient V·O2 kinetics, despite similarities of V·O2max and VT. This is attributable to the greater volume of training performed by LD runners. Further investigations into adaptation(s) to training in muscle in MD and LD runners is required to determine the functional significance of such differences and the response of V·O2 kinetic parameters to different training stimuli.